The impact of extreme-right parties on immigration policy in Italy and France in the early 2000s - Carvalho, J. (Comparative European Politics, 2016)
In May 2001, the Italian Lega Nord (LN) was included in the coalition government led by Silvio Berlusconi after the general election. A year later, the French Front National (FN) provoked a political earthquake after the passage of Jean-Marie Le Pen to the second round of the 2002 presidential ballot, alongside the incumbent President Jacques Chirac. Drawing from a qualitative methodology, this article compares the LN’s and the FN’s impact on the development of Italian and French immigration policies during Berlusconi’s second term and President Chirac’s last term. Acknowledging the complexity of immigration policy, the article concludes that the LN had a moderate impact in Italy while the FN enjoyed significant impact on policy developments in France. This research highlights the presence of important endogenous and exogenous constraints on the development of this political process in the two cases, which have been neglected in the ERP literature.